Ageing and complexity - Laura Formenti; Davide Cino; Francesca Loberto (European Journal for Research on the Education and Learning of Adults)
This paper presents a critical literature review on the systemic interconnections between ageing, learning, and care. Using the lenses of complexity and interdisciplinarity, we analysed a sample of 62 papers published between 2003 and 2022, examining their reference to micro, meso and/or macro levels, theoretical depth, and use of complexity as a sensitizing concept to understand implications for learning and transformation as structural features of an ageing society. Our analysis highlighted the role of different settings of care (formal, informal, and technology-mediated) in shaping, enhancing, or hindering meaning, well-being, and social justice for older learners and their caregivers, and the implications for society at large. Findings suggest a gap in the examined literature regarding the use of complexity theories to highlight self-organisation, interdependence, and co-evolution of individual and systemic learning. A theoretical interdisciplinary framework, we contend, would better mirror the multiple factors and levels entailed in the process of ageing.